Analgesic Effects of the Aqueous Lemon Verbena Extract in Rats - Veisi, M.; Shahidi, S.; Komaki, A.; Sarihi, A. (Нейрофизиология, 2016)
Lemon verbena (vervain, LV) is used in traditional folk medicine as a remedy against asthma, spasms, cold, fever, pain of different genesis, insomnia, etc., but its effects have not been examined experimentally. We studied effects of an aqueous extract of leafs of this plant on the parameters of nociception-related tests, tail-flick, and writhing ones. The first aqueous extract of LV leafs was prepared and dried. Wistar rats were randomly divided into seven experimental groups, which received i.p. injections of saline (control), LV extract (10, 100, 500, and 1000 mg of dry substance per 1 kg of the body mass), morphine, and 1000 mg/kg of the LV extract + naloxone. Injections of 500 and 1000 mg/kg of the extract significantly increased the tail-flick latency, as compared to that in the control group (P < 0.001). The number of writhings per one hour decreased after injections of the extract (100-1000 mg/kg). The maximum analgesic effects of the extract were comparable with those of morphine (10 mg/kg). Naloxone completely abolished the effect of the LV extract in the tail-flick test and partly suppressed such action in the writhing test. Thus, our experiments demonstrated noticeable anti-nociceptive effects of the aqueous LV extract; possibilities for application of this extract or its derivatives in pain management should be examined.